2021
DOI: 10.3390/ijms22063223
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin Promotes Osteogenesis and Modulates Collagen Matrix Organization and Mineralization In Vitro and In Vivo

Abstract: This study evaluated the direct effect of a phytochemical, hesperidin, on pre-osteoblast cell function as well as osteogenesis and collagen matrix quality, as there is little known about hesperidin’s influence in mineralized tissue formation and regeneration. Hesperidin was added to a culture of MC3T3-E1 cells at various concentrations. Cell proliferation, viability, osteogenic gene expression and deposited collagen matrix analyses were performed. Treatment with hesperidin showed significant upregulation of os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 46 publications
4
36
0
Order By: Relevance
“…Phytochemicals, particularly flavonoids, are gaining increased interest for their therapeutic potential for bone. Studies reporting the effects of flavonoids in cell culture and animal models have strongly supported a role for flavonoids in bone formation and resorption in vitro and in vivo [19,22,25,27]. Additionally, the intake of flavonoids has been shown to improve bone health not only due to an influence in osteogenesis and osteoclastogenesis, but also due to their antioxidant and anti-inflammatory properties [26,27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phytochemicals, particularly flavonoids, are gaining increased interest for their therapeutic potential for bone. Studies reporting the effects of flavonoids in cell culture and animal models have strongly supported a role for flavonoids in bone formation and resorption in vitro and in vivo [19,22,25,27]. Additionally, the intake of flavonoids has been shown to improve bone health not only due to an influence in osteogenesis and osteoclastogenesis, but also due to their antioxidant and anti-inflammatory properties [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…In order to evaluate the effect of HE on osteoclasts and bone homeostasis in vivo, two studies were conducted: a model of inflammatory bone loss in the alveolar housing and a skeletal bone phenotype characterization after a long (determined as enough time to affect bone connective tissue and cell function-6 weeks and 12 weeks) dietary supplementation with HE. HE has been shown to affect bone mass in rodents primarily due to inhibition of osteoclastogenesis, although there are reports that it may increase the number of osteoblasts and increase osteoblast function at low doses as well [19,22,23,25,30]. The mouse model of periodontal inflammatory bone resorption used in our study was chosen based on an acute-to-chronic inflammatory response to interdentally placed ligature [42,43] without the introduction of virulent factors such as pathogenic periodontal bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, hesperidin protected bone mass loss by alleviating oxidative stress and inflammation in an ovariectomy rat model ( Zhang et al, 2021 ). Hesperidin could upregulate the expression of osteogenic markers and promote the maturation of bone organic matrix, thus exerting anti-osteoporosis effects in vitro and in vivo ( Miguez et al, 2021 ). In an experimental rat model, hesperidin intake resulted in bone mass gain in young rats and protected against ovariectomy-induced bone loss in adult rats, as well as reduced oxidative stress and total lipid content ( Horcajada et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hesperidin, a flavanone glycoside highly abundant in citrus fruits, has exhibited a protective role in osteoporosis through enhancing osteogenic differentiation and inhibition of osteoclastogenesis ( Liu et al, 2019 ; Miguez et al, 2021 ; Zhang et al, 2021 ), but little is known about the role of hesperidin in the dexamethasone-induced osteoporosis. Zhang et al indicated that hesperidin showed enhanced osteogenic differentiation and partially reversed dexamethasone-induced inhibition of osteogenic differentiation by p53 signaling pathway in vitro , suggesting the compound may be a promising candidate against dexamethasone-induced osteoporosis ( Zhang et al, 2021 ).…”
mentioning
confidence: 99%